Interfaces between bariatric surgery and oral health: a longitudinal survey - Marsicano,Juliane Avansini (2011)
PURPOSE: To evaluate oral changes, such as dental caries, periodontal disease, dental wear and salivary flow in bariatric patients. Fifty four obese patients who underwent bariatric surgery were studied before (n=54), up after 3 months (n=24) and 6 months (n=16). METHODS: Indices for evaluating oral conditions were: DMFT, CPI, DWI and salivary flow. OIDP questionnaire was used to assess the impact of oral health on quality of life. ANOVA and Spearman correlation were used (p<0.05). RESULTS: DMFT was 17.6±5.7, 18.4±4.1 and 18.3±5.5 (P>0.05), presence of periodontal pockets in 50%, 58% and 50% of patients (p>0.05), tooth wear in dentin present in 81.5%, 87.5% and 87.5% before, 3 and 6 months after surgical treatment respectively. There were differences between the three periods for prevalence and severity of dental wear (p = 0.012). Salivary flow was 0.8±0.5 ml/min before surgery, 0.9±0.5 ml/min for 3 months and 1.1±0.5m/min for 6 months (p>0.05). The impact of oral health on quality of life decreased with time after bariatric surgery (p= 0.029). CONCLUSION: The lifestyle changes after bariatric surgery and these changes may increase the severity of pre-existing dental problems. However, these alterations in oral health did not influence the quality of life.